INTERGENERATIONAL RELATIONSHIPS AND SOCIAL ISOLATION OF OLDER ADULTS IN RURAL CHINA. (11th November 2018) - Yu, K; Chi, I
Abstract: Previous work has identified protective/risk factors for social isolation among older adults, yet few examined the role of intergenerational relationships. This paper uses wave-6 data to scrutinize the association between different types of intergenerational relationships and social isolation of rural older adults in Anhui, China. Participants with no children were excluded from this analyses (N=1, 184). Social Isolation is measured by Lubben Social Network Scale. Multiple regressions controlling for covariates were conducted to test 6 types of intergenerational relationships (mutual emotional, conflict relations, upwards and downwards monetary, upwards and downwards instrumental). The sample's mean age is 70.82, 62.58% have no education, 68.50% are married and 19.43% live alone. Only mutual emotional support (B=0.51, SE=0.08, p<.001) and upwards instrumental support (B=1.96, SE=0.54, p<.001) were negatively associated with older adults' social isolation. Intervention programs aim to address social isolation may consider adopting an intergenerational approach with emphasis on emotional and instrumental support.